Research progress on nonsteroidal anti-inflammatory drugs in the treatment of pituitary neuroendocrine tumors - Li, Jiaqi; Shi, Xinkang; Tang, Tao; Zhou, Manxin; Ye, Feng (Frontiers in Pharmacology, 2024)
Pituitary neuroendocrine tumor is the third most common primary intracranial tumor. Its main clinical manifestations include abnormal hormone secretion symptoms, symptoms caused by tumor compression of the surrounding pituitary tissue, pituitary stroke, and other anterior pituitary dysfunction. Its pathogenesis is yet to be fully understood. Surgical treatment is still the main treatment. Despite complete resection, 10% to 20% of tumors may recur. While dopamine agonists are effective in over 90% of prolactinomas, prolonged use and individual variations can lead to increased drug resistance and a gradual decline in efficacy, which ultimately requires surgical intervention. Nonsteroidal anti-inflammatory drugs reduce the production of inflammatory mediator prostaglandins by inhibiting the activity of cyclooxygenase and exert antipyretic, analgesic, antiplatelet, and anti-inflammatory effects. In recent years, many in-depth studies have confirmed the potential of nonsteroidal anti-inflammatory drugs as a preventive and antitumor agent. It has been extensively utilized in the prevention and treatment of various types of cancer. However, their specific mechanisms of action still need to be fully elucidated. This article summarizes recent research progress on the expression of cyclooxygenase in pituitary neuroendocrine tumors and the treatment of nonsteroidal anti-inflammatory drugs. It provides a feasible theoretical basis for further research on pituitary neuroendocrine tumors and explores potential therapeutic targets.